Sebuah Perancangan Sistem Informasi Pemasaran dan Penjualan Lukisan pada Polesan Art Galeri - Ramdani Quraiss hihab (Universitas Multimedia Nusantara, 2019)
Abstract— This research was conducted to design a web-based painting sales information system design in an art gallery. The research method used in this study uses descriptive methods, namely by explaining the phenomena that occur from data collected through observation and interviews. And using a structured approach method and for system development using the waterfall method. The results of this study are website-based painting sales application designs in art galleries. Currently the painting marketing process is still limited to certain areas, which makes it difficult to increase the sales volume of paintings when tourists visit a little, and consumers are required to come directly to the gallery to make transactions so consumers who don't have time to buy paintings in art galleries. Thus to improve the marketing process and make it easier for consumers to buy paintings anytime and anywhere, then design web-based marketing and sales information systems. The design of this marketing and sales information system aims to improve marketing by disseminating information about products to be sold and providing services to consumers to make purchases that can be done anywhere and ultimately will provide maximum service which will ultimately increase revenue from art galleries. polished.